Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1080/02791072.2007.10399877
|View full text |Cite
|
Sign up to set email alerts
|

A Faith-Based Intervention for Cocaine-Dependent Black Women

Abstract: The purpose of the present study was to obtain preliminary data on the effectiveness of a faith-based treatment adjunct for cocaine-using homeless mothers in residential treatment. The Bridges intervention utilizes various Black church communities to provide culturally-relevant group activities and individual mentoring from volunteers. Eighteen women who were recent treatment admissions were randomly assigned to receive Standard Treatment plus Bridges or Standard Treatment with an Attention Control. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 33 publications
1
40
1
Order By: Relevance
“…Bridges uses the church as a sustainable social network with supportive mentors who help recovering women to maintain abstinence following treatment. Results from two evaluations were promising (Stahler et al, 2005(Stahler et al, , 2007. Such an intervention strategy could be adapted for alcohol use disorder treatment for African American women.…”
Section: Implications and Future Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Bridges uses the church as a sustainable social network with supportive mentors who help recovering women to maintain abstinence following treatment. Results from two evaluations were promising (Stahler et al, 2005(Stahler et al, , 2007. Such an intervention strategy could be adapted for alcohol use disorder treatment for African American women.…”
Section: Implications and Future Researchmentioning
confidence: 98%
“…The "SISTAS" group-based alcohol misuse prevention intervention that incorporates both racial identity and spirituality could be used in such a context (McCurtis Witherspoon & Williams Richardson, 2006). "Bridges to Community" is a faith-based intervention for African American women dependent on cocaine (Stahler et al, 2005(Stahler et al, , 2007. Bridges uses the church as a sustainable social network with supportive mentors who help recovering women to maintain abstinence following treatment.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Empirical investigations aimed at increasing treatment retention rates for AfA women have focused on the efficacy of clinical services targeted at client factors such as religiosity (Stahler et al, 2007), low socioeconomic status (Bride & Humble, 2008), and lack of transportation (Dakof et al, 2003). Results of these studies have shown that changing treatment programming to address char acteristics unique to the target population can help improve treat ment retention.…”
Section: Treatment Retention and Working Alliancementioning
confidence: 99%
“…Descriptive studies, studies not reported in English, and those not conducted in the United States were also excluded. After these exclusions, eight studies remained for inclusion in the present review (57)(58)(59)(60)(61)(62)(63)(64).…”
Section: Methodsmentioning
confidence: 99%